Pemanfaatan Hasil AKMI Untuk Pembelajaran Berkelanjutan di Madrasah - Suryadi, Ahmad (Jurnal Pelita Manajemen Pendidikan, 2024)
Since 2020, the Ministry of Religious Affairs of the Republic of Indonesia has made a very fundamental effort to improve the quality of madrasah, namely by conducting the Indonesian Madrasah Competency Assessment (AKMI), which includes 4 literacies, namely reading literacy, numeracy literacy, socio-cultural literacy through a fairly rigorous selection. Data shows that the results of AKMI from 2020 to 2023 show quite encouraging results. The AKMI learning improvement model, which begins with an assessment and continues with training madrasah teachers to improve learning in the classroom, has proven to be very effective, so it is necessary to maintain and improve the quality of AKMI implementation in the coming years.